Low glomerular filtration rate is a risk factor for ribavirin‐associated anaemia in old patients with chronic hepatitis C. Issue 4 (22nd October 2012) - Borroni, G.; Cazzaniga, M.; Andreoletti, M.; Ceriani, R.; Guerzoni, P.; Omazzi, B.; Pich, M. G. L.; Prada, A.; Spinzi, G.; Terreni, N.; Salerno, F.
Summary Elderly patients with chronic hepatitis C have a reduced responsiveness to antiviral therapy with Peg‐interferon and ribavirin. The dose reduction or the discontinuation of ribavirin due to the occurrence of anaemia is one of the most important causes for the low sustained viral response observed in older patients. We aimed to evaluate the relationship between baseline renal function and the early onset of ribavirin‐associated anaemia in older (≥60 years) patients. Using data from 348 patients with chronic hepatitis C consecutively treated with peg‐interferon plus ribavirin, we investigated which factors were associated with the occurrence of anaemia in elderly patients (≥60 years). Ribavirin‐induced anaemia occurred in 40.5% of patients. Older patients showed a rate of anaemia significantly higher than younger patients (51.5% vs 36.3%; P = 0.009). Consequently, the rate of ribavirin dose reduction or discontinuation due to anaemia was 35.1% in older patients and 23.5% in younger patients (P = 0.029). A significantly higher proportion of older patients had a low baseline glomerular filtration rate (GFR) compared with younger patients (56.7% vs 27.1%; P < 0.001). At the multivariate regression analysis, low baseline GFR (<70 mL/min) was associated with an increased risk of ribavirin‐associated anaemia only in the older patients (OR: 3.526; 95% CI: 1.385–8.979; P = 0.008). In this subset, baseline GFR was significantly correlated with both absolute (r = −0.320; P < 0.001) and relative (r = −0.324; P < 0.001) haemoglobin decrease within the first 8 weeks of treatment. In patients aged >60 years, a low pre‐treatment GFR was strongly associated with the risk to develop ribavirin‐related anaemia with consequent reduction in ribavirin doses.